An intersectional reflexive account on positionality: researching Pakistani and Bangladeshi Muslim lone motherhood - Baz, Sarah A (Qualitative research : QR, 2024)
Engaging in ‘reflexive practice’ throughout the research process (Benson and O’Reilly, 2022) and a ‘reflexivity of discomfort’ (Hamdan, 2009) through an intersectional lens, this article presents a reflective account of accessing and conducting observations and interviews at a South Asian women’s organisation, in North England, to explore Pakistani and Bangladeshi Muslim (PBM) lone motherhood. It critically explores how researchers’ own subjectivities and intersecting identities – in this case, my intersecting identities and positionalities as a young British Pakistani Muslim women, researcher and volunteer – impact interactions in different circumstances with different groups of participants and the importance of having continuous critical self-awareness. Moving beyond simplistic insider–outsider debates, the paper contributes towards further developing reflexivity debates taking an ‘intersectional reflexivity’ approach. It argues for thinking about the research process and engagements in the field as socially constructed, changing, adapting and negotiated overtime and to utilise intersectionality to unpick broader categories. Finally, it encourages researchers to adopt reflexivity in their research practices.